ANALYSIS OF THE EFFECTIVENESS OF LEARNING-BASED VIDEO TECHNOLOGY AT THE SCHOOL LEVEL - Zainul Hafizi (Jurnal Scientia, 2023)
The study aims to analyze the effectiveness of video technology-based learning in thematic subjects at the primary school level. The learning process can also be enjoyable, with an awareness of utilizing available innovations properly and as needed. This research employs qualitative research methods or library research, involving reading books, articles, and literature related to the effectiveness of video technology-based learning. The results of this study indicate that the utilization of video technology for learning thematic subjects at he school level has a positive impact on students’ understanding of concepts and their interest in learning. The students provided positive feedback, such as being more active in the classroom, enhanced practical understanding, and improved academic achievement.